Debates on Civilization in the Muslim World: Critical Perspectives on Islam and Modernity by Lutfi Sunar, ed. (New Delhi: Oxford University Press, 2017. 434 pages.) (American Journal of Islam and Society, 2017)
“Civilization,” which plays a significant role in today’s world, is a termthat has been discussed and debated through the ages and remains so today.In the broader context, and at different levels and contexts (e.g., historical,cultural, and political), it is used to describe “the entirety of collective90human values”; “consequential behavior against barbarism” (or simply “theidea of being civilized”); as a “vision of existence and order”; and, aboveall, as “being an abstraction of modernity and secularism.” One of the mostoft-debated concepts in the social sciences, it has largely been framed byWestern assumptions and concerns; although there are non-Western perspectiveson it as well. A recent addition to the multi-faceted debate on civilizationand modernization vis-à-vis the Muslim world is editor LutfiSunar’s Debates on Civilization in the Muslim World. Sunar is a Turkishsociologist who teaches at Istanbul University.This collective endeavor of (predominantly young) Muslim scholarsseeks to evaluate Muslim views on civilization by challenging the “embeddedprejudices within the social theory” and offering “alternative viewpoints”(p. vii). It presents “a complex assessment of key ideas in themodernist discourse from non-ethnocentric perspectives and offers a newunderstanding of civilization” (p. viii).To achieve this objective, the book has been divided into three mainparts. Part 1, “Defining and Discussing Civilization,” consists of threechapters, by Anthony Pagden, Lutfi Sunar, and Mustafa Demirici, respectively,that review, analyze, and discuss definitions of civilization andmodernity and their “Eurocentric” understandings. Part 2, “Debates on theCivilization in the Contemporary Muslim World,” examines non-Westerncivilizations, efforts to resist against being assimilated in Western perspectivesand dominance. These chapters are contributed by Vahdettin Isik,Cemil Aydin, Necmettin Dogan, Halil Ibrahim Yenigun, Seyed Javad Miri,Mahmud Hakki Akin, and Driss Habti, respectively. Part 3, “Modernization,Globalization, and the Future of Civilization Debate,” features chaptersby Syed Farid Alatas, Yunus Kaya, Murat Cemrek, and KhosrowBagheri Noaparast, respectively. The volume’s overall theme is designed“to expose complex issues for further discussion pertaining to modernization,globalization, (de)colonization, and multiculturalism” (p. vii). As it isdifficult to focus on all the chapters, I provide a brief assessment of someselected ones below ...